LANDSLIDE SUSCEPTIBILITY MAPPING OF THE NORTHEASTERN PART OF ACHAIA PREFECTUREUSING ANALYTICAL HIERARCHICAL PROCESS AND GIS TECHNIQUES - Rozos, D.; Bathrellos, D.G.; Skilodimou, D.H. (Bulletin of the Geological Society of Greece, 2010)
Landslides are one of the most frequent and disastrous natural hazards worldwide. Thus, the need of landslide susceptibility maps is of primary importance as they are both a useful tool for the land use planning and a necessary step for future development activities. This paper presents an integrated technique of analytical hierarchical process (AHP) and geographic information system (GIS) to create a landslide susceptibility map of the NE part of Achaia prefecture. The study area mainly consists of Neogene deposits and it is a part of the Corinthian graben, which characterized by intense neotectonic activity. Therefore, it is affected by many slope movements that usually cause serious damages in inhabitant areas and road networks. Based on field survey data analysis six parameters were chosen as major parameters that influence the stability of slopes to the direction of landslide manifestation. The AHP method identifies both the rate of the individual classes, and the weight of each factor. Spatial layers with their corresponding rates and weights were linearly combined to prepare the landslide susceptibility map, which includes four zones of slope movement’s susceptibility, namely a low, a moderate a high and a very high zone. The evaluation and final confirmation of the map was based on a great number of recorded landslides in the area.